Legal Protection for Buyers of Joint Assets Sold Without Wife's Consent - Andi Dimah Laila Nurfaiqah; Tjempaka Tjempaka (Susbtantive Justice International Journal of Law, 2023)
This article aims to provide an objective explanation of the legal protection afforded to buyers who intend to transfer rights to land that is jointly owned without the wife's consent. In 2012, the late Haryanto sold the land to PT. Makmur Persada Indonesia conducted the transaction as recorded in Sale and Purchase Deed No. 53/2012, prepared by Notary/Land Deed Maker Hj. Hasnawati Juweni Shande. In 2017, Sherly initiated legal action asserting that the deed for the land sold by the deceased Haryanto reflected joint ownership resulting from his marriage to Sherly; yet, the relevant sale and purchase transaction occurred without Sherly's involvement despite her rights to the property. Normative research was conducted utilising a statutory, conceptual, and case approach. The research specifically analysed secondary data, comprising primary and secondary legal materials, which was analysed descriptively. In relation to Sherly's lawsuit, the Serang District Court issued decision Number 39/Pdt. Srg, which resulted in the rejection of the plaintiff's application. Subsequently, the plaintiff lodged an appeal against the Serang Court's decision. In 2018, Decision Number 39/Pdt/2018/PT BTN of the Banten High Court upheld the Serang District Court's decision to reject the applicant's claim entirely. The Supreme Court confirmed this judgement in 2019 with Judicial Review Decision Number 227K/Pdt/2019, thus dismissing the plaintiff's lawsuit. Thus, it seems that the verdict of dismissing the plaintiff's application safeguards the buyer.